An optimal battery allocation model for battery swapping station of electric vehicles. (1st June 2023) - Yang, Jie; Liu, Wei; Ma, Kai; Yue, Zhiyuan; Zhu, Anhu; Guo, Shiliang
Abstract: This paper studies battery of battery charging station (BSS) orderly swapping, efficient battery management and reasonable battery allocation. Firstly, based on a user-centered perspective, this paper first establishes the user adaptive response model according to the battery state of health (SOH) and state of charge (SOC) after battery allocation to realize the user autonomous decision-making. Secondly, the battery exchange priority function is established for the ordered exchange of BSS and EV batteries during the battery exchange process. Thirdly, the batteries in the BSS are divided into three battery libraries to be managed according to the difference of battery SOH so that the batteries are accurately and efficiently allocated to the power system and EV services. Finally, BSS transfers excess electricity to the power system through battery to grid (B2G) technology as regulating energy, increasing the flexibility of the power system. Through the analysis of the optimization model, the results show that compared with the random distribution of batteries, the model not only increases the benefits of BSS, but also ensures the distribution of each battery is rapid, accurate and reasonable, realizing the rational use of batteries. Highlights: A two-layer scheduling model for the battery swapping process is proposed. The addition of the battery swapping criterion makes it more reasonable. Battery swapping stations can serve the power system and electric vehicles. Maximize the profitability of battery swapping stations.